2015
DOI: 10.1039/c4dt03123g
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY functionalized o-carborane dyads for low-energy photosensitization

Abstract: A new type of organic dyad that can induce low-energy photosensitization has been developed; electron donor and electron acceptor units are boron dipyrromethene (BODIPY) and ortho-carborane (o-Cb), respectively. The new dyads consist of a V-shaped BODIPY-(o-Cb)-BODIPY molecular array in which two BODIPY units are substituted onto two adjacent carbon atoms of the central o-Cb. In the presence of the o-Cb unit, as an electron acceptor, significant fluorescence quenching was observed which indicated that photoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 55 publications
(21 reference statements)
1
30
1
Order By: Relevance
“…6,[8][9][10] This quenching takes place due to a rapid photoinduced electron-transfer (PET) process from the excited state S 1 of the fluorophore to the lower energy excited state S x of the cluster, which inhibits the fluorescence emission of the fluorophore. 11 In 2007, our group reported the PL properties of o-carboranyl-functionalized large molecules based on poly(aryl-ether) derivatives, 12,13 In these systems, the influence of the cluster (neutral closo clusters or their conceptually derived anionic nido clusters that are formally obtained by the removal of a B + ) on the fluorescence behavior was investigated. More recently, we developed a set of fluorescent dyads based on carboranes (see compounds 1-2 in Scheme 1) in which the styrene fragment is bound to at least one of the C c atoms through a bridging methylene.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] This quenching takes place due to a rapid photoinduced electron-transfer (PET) process from the excited state S 1 of the fluorophore to the lower energy excited state S x of the cluster, which inhibits the fluorescence emission of the fluorophore. 11 In 2007, our group reported the PL properties of o-carboranyl-functionalized large molecules based on poly(aryl-ether) derivatives, 12,13 In these systems, the influence of the cluster (neutral closo clusters or their conceptually derived anionic nido clusters that are formally obtained by the removal of a B + ) on the fluorescence behavior was investigated. More recently, we developed a set of fluorescent dyads based on carboranes (see compounds 1-2 in Scheme 1) in which the styrene fragment is bound to at least one of the C c atoms through a bridging methylene.…”
Section: Introductionmentioning
confidence: 99%
“…This result implies that all compounds have a significant electronic coupling between the two organic chromophores in the ground state. 34,35 The solvent dependence of the UV-vis absorption spectra for CDC, CDN, CDO and CDS was hardly observed (Fig. S1, ESI †), further indicating that the ground state was not affected by the solvent polarity.…”
Section: Design and Synthesis Of The Compoundsmentioning
confidence: 99%
“…46 (2 H, d, J = 8.0 Hz), 7.36-7. 35 (2 H, d, J = 4.0 Hz), 7.30-7.22 (6 H, m), 1.20 (6 H, s). 13 Synthesis of 1,2-di(dibenzothiophene-2-yl)-ortho-carborane, CDS.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…143a-b, Scheme 34) for low-energy photosensitization. 52 The new dyads consist of V-shaped molecules in which two BODIPY units are substituted onto two adjacent carbon atoms of the central o-carborane. In the presence of the o-carborane unit, as an electron acceptor, significant fluorescence quenching was observed which indicated that PET (photoinduced electron transfer) had occurred from the end-on BODIPY units to the central o-carborane with PET efficiencies of B63-71%.…”
Section: Luminescent Carborane-fluorophore Conjugatesmentioning
confidence: 99%